“Help me help you”: designing visual teaching tools for the Autism Spectrum Disorder (ASD) children / Muhamad Hafiz Hassan … [et al.] - Hassan, Muhamad Hafiz; Emeih Wahed, Wan Juliana; Wardi, Rainal Hidayat; Abdullah Abdullah, Mohamad Hariri; Isa, Badrul; Ahmad, Muhammad Fakhruddin (Faculty of Art and Design, 2023)
Children with ASD have difficulty with social imagining, which affects their communication ability, social skills, and behaviour. The purpose of this study is to evaluate the design characteristics of visual teaching tools used by instructors for ASD children, utilising the two elements of the VARK model: visual and kinesthetic. The effectiveness of learning sessions is dependent on the selection and deployment of teaching instruments that can provide ASD children with a better learning experience and stimulate engagement and communication during learning. Thus, a qualitative technique was used to investigate the ASD instructor’s perspective on the visual teaching tools to support children with ASD using one-on-one and in-depth interview questions. The findings revealed that natural and pastel colours are the best choices for children with ASD, and materials that provide sensory help ASD respond appropriately. Future product designers can consider the colour selection, materials used, and type of teaching materials to attract children’s attention while also contributing to their positive development, which allows them to think, solve problems, and be creative in a fun learning environment. Researchers should use the VARK model in the future to investigate how well children with ASD perform in auditory and reading skills.